PP.37.19: SYMPATHETIC OVERACTIVITY IN HYPERTENSIVE PATIENTS WITH SLEEP APNOEA-HYPOPNEA SYNDROME. (June 2015) - Milanov, S.; Vuckovic-Filipovic, J.; Davidovic, G.; Cekerevac, I.; Iric-Cupic, V.; Miloradovic, V.; Simic, I.; Simovic, S.; Petrovic, M.; Pavlovic, M.; Vuleta, M.
Abstract : Objective: Patients with sleep apnoea-hypopnea syndrome show very high levels of sympathetic activity, which may affect both short-term and long-term blood pressure regulation. Spectral analysis of heart rate variability allows simple, non-invasive testing of the autonomic function. Aim was to determine the level of sympathetic activity using spectral analysis of HRV in hypertensive patients with/without SA. Design and method: Research included 100 patients who underwent polysomnograpic examination in UCC Kragujevac. According to apnoea-hypopnea index (AHI) all patients were divided into 3 equal groups, 25 patients in each group (AHI 5–15; 15–30 and > 30). Fourth group was a control group with 25 patients without SA. All patients were evaluated for prior hypertension and antihypertensive therapy. Diagnosis was confirmed using ABPM and HTN was classified according to the latest guidelines. Spectral analysis of HRV was used for non-invasive testing of autonomic function. The analysis was performed using a fast Fourier transform of the autoregression method integrated into 24 h ECG Holter monitoring. All data were statistically analyzed in the SPSS for Windows. Results: Study population consisted of 69% of male and 31% of female patients with mean age of 55.05 ± 11.16 years. Prior hypertension was present in 76% of patients (x2 = 27.04; p = 0.000), with 68% on antihypertensive therapy (x2 = 12.96; p = 0.000). Among patients with diagnosed SA 62% had hypertension (x2 = 7.31; p = 0.007). More than 50% of patients had beta blockers in their therapy in total popultion and 46% in group with SA. Spectral analysis of HRV showed higher sympathetic activity: LF component – 984.29 ± 3893.04 vs HF component – 464.04 ± 1938.75. LF/HF ratio was >2.0 in 70% of patients confirming that autonomic balance is shifted towards sympathetic activity (x2 = 12.96; p = 0.000). Among patients using beta blockers 66.1% had higher sympathetic activity. Conclusions: As previously described, males have sleep apnoea-hypopnea syndrome more often than females. More than a half of patients with sleep apnoea had prior hypertension. Autonomic balance was shifted towards sympathetic activity. Although majority of patients in both groups, total and patients with sleep apnea, had beta blockers in therapy, sympathetic activity remained higher.